2010
DOI: 10.1523/jneurosci.5120-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor and Epidermal Growth Factor Activate Neuronal m-Calpain via Mitogen-Activated Protein Kinase-Dependent Phosphorylation

Abstract: Calpain is a calcium-dependent protease that plays a significant role in synaptic plasticity, cell motility, and neurodegeneration. Two major calpain isoforms are present in brain, with -calpain (calpain1) requiring micromolar calcium concentrations for activation and m-calpain (calpain2) needing millimolar concentrations. Recent studies in fibroblasts indicate that epidermal growth factor (EGF) can activate m-calpain independently of calcium via mitogen-activated protein kinase (MAPK)-mediated phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 47 publications
5
107
0
Order By: Relevance
“…Thus, it has been shown that calpain 2, but not calpain 1, was activated by ERKmediated phosphorylation under certain experimental conditions (59,60,61). Because the ERK signal transduction pathway is highly activated in the presence of Aβ in mature central neurons, it is possible that this mechanism could play a role in the generation of the 17-kDa tau in AD 20,22).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been shown that calpain 2, but not calpain 1, was activated by ERKmediated phosphorylation under certain experimental conditions (59,60,61). Because the ERK signal transduction pathway is highly activated in the presence of Aβ in mature central neurons, it is possible that this mechanism could play a role in the generation of the 17-kDa tau in AD 20,22).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in hippocampal slices from adult rats showed that BDNF mediates the thetaburst stimulation-induced increase in actin polymerization in dendritic spines, through regulation of p21-activated kinase (PAK) and ADF (actin-depolymerizing factor)/cofilin ). An increase in actin polymerization in spines may also arise from activation of m-calpain through ERK-dependent phosphorylation, as shown in cultured neurons (Zadran et al, 2010). F-actin polymerization in spines plays a key role in LTP maintenance in vivo (Fukazawa et al, 2003) and, therefore, these alterations may underlie some of the effects of BDNF in long-term synaptic potentiation.…”
Section: Bdnf and Spine Plasticitymentioning
confidence: 99%
“…In addition to activity-induced elevation in intracellular Ca 2ϩ , calpain is also activated by BDNF signaling (Zadran et al, 2010a). Seizure-induced upregulation of BDNF/TrkB signaling (Binder et al, 2001;Rivera et al, 2002) and activity-dependent endogenous release as well as exogenous application of BDNF (Rivera et al, 2002(Rivera et al, , 2004Wake et al, 2007), all have been shown to downregulate KCC2 protein and function, demonstrating a critical role for TrkB activation in activity-dependent downregulation of KCC2.…”
Section: Enhanced Degradation Of Kcc2 Leads To Fast Changes In Gabaermentioning
confidence: 99%
“…4) indicate that a fraction of KCC2 is resistant to calpain within the time window of the present experiments. Curiously, BDNF-calpain signaling has been proposed to regulate spine plasticity (Zadran et al, 2010a). Since spines are known to express high levels of KCC2 (cf.…”
Section: Enhanced Degradation Of Kcc2 Leads To Fast Changes In Gabaermentioning
confidence: 99%